Fantastic contraptions - Isogawa, Yoshihito, 1962- (San Francisco, CA : No Starch Press, 2011)
"The book is color throughout, with little to no text accompanying its diagrams ... The LEGO technic idea books are for anyone who wants to create a moving masterpiece, as well as those who want to make original robots with MINDSTORMS. It can also be used to demonstrate how machines work and to experience the fun of mechanics."--Publisher description.
Four-legged walkers -- Six-legged walkers -- Two-legged walkers -- Using wind -- Using weights -- Movement through vibration -- Using springs -- Using magnets -- Using lights -- Using pneumatics -- Using solar panels -- Chairs and tables -- Off-center axis of rotation -- Intermittent movement -- Changeover mechanisms -- Changeover by switching a motor's rotational direction -- Mystery.
Keywords: Mobile robots; LEGO toys